The Round Table, 1910-66 - May, A (1995)
This thesis traces the history of the London Round Table group and of the Round Table magazine from their origins in 1909-10 until the decision to launch a "new" Round Table in 1966. It takes as its focus the ideas put forward by members of the group, in the Round Table and elsewhere, on a range of Imperial and international problems. It utilises knowledge on the authorship of Round Table articles in order to clarify the processes by which Round Table policy was made, and the role of different individuals within the group. It examines the rôle of the Round Table as a pressure group for Imperial reform and in particular its relationship to Empire federalism, seeking to elucidate the extent to which it was able to act coherently, and attempting to describe its aims, methods and influence. On the question of federalism, the thesis finds an inability to agree on details, but also a continuing belief in the necessity for constitutional unit until the late 1940s. It suggests that this belief was not entirely unrealistic. The thesis argues that, despite differences of emphasis, the Round Table was able to develop a distinctive ideology of Imperialism which was strongly supportive of the Imperial rôle yet also responsive to the need for change. It finds that the group was only briefly influential on government policy, under Lloyd Georfge's administration, but it argues that the group saw its main purpose as that of influencing long-term opinion rather than short-term policy. It suggests that the group was able to play an important mediating rôle, between conservatism and radicalism, and between policy-making and opinion.